2011 Annual Report: Working together for impact. - CGIAR Challenge Program on Water and Food (2012)
The 2011 Annual Report describes the achievements in each of the six rivers basins and how they are each responding to a well-defined development challenge. Stories and highlights from the basins elaborate on the messages.